(untitled) (International Journal of Engineering and Computer Science, 2015)
High Efficiency Video Coding (HEVC) is recent digital video coding standard of the ITU-T committee. The main goal of the HEVC standardization was to increase significant compression performance compared to H.264 standards in the range of fifty percentage bit-rate reduction for equal perceptual video quality. In this project we have developed and evaluated the performance of HEVC decoder for lossless I-frames decoding. Subjective and objective quality metrics of the compressed medical ultrasound video samples of different resolutions are evaluated. We also experimentally measured the performance of the HEVC decoder for medical ultrasound video sequences. The results show that, with HEVC decoding of the ultrasound video samples, equivalent clinical quality videos can be obtained with values of the quantization parameters in range up to 36 with PNSR ratios.